Walkability; The Relationship of Walking Distance, Walking Time and Walking Speed - Silitonga, Shanty (Fakultas Teknik Universitas Katolik Santo Thomas, 2020)
Walking is cheap and healthy. It is the main transportation for the majority of students exploring their daily life in their campus area. Different types of people will have various types of walking behavior. To develop a better knowledge of the walkability of built environment, it is important to understand the complexity behind walking behavior. There are many possible factors in measuring walking behavior. Walking behavior can be measured by walking speed, walking directions, walking experiences, group formation, and density. In this research paper, only three factors are going to be used to testify the descriptive study of walking behavior on the campus of UNIKA St Thomas University; which are walking distance, walking time and walking speed. The method used in this study is known as walking distance test, and the data were analyzed using the comparative approach. The findings show that walking speed, walking time and walking speed are deeply related to each other. The results of the observation study of walking behavior revealed that the condition of the campus built environment related to the density, connectivity, and land-use diversity seem to influence the amount and variety of walking activities that occur in the given environment and also affect how the walking activities conducted. The researcher concluded that walking speed, walking time and walking distance the pedestrian in campus UNIKA St.Thomas are comfortable based on the related theories.